Does living in a food insecure household impact on the diets and body composition of young children? Findings from the Southampton Women's Survey. Issue 6 (7th June 2011) - Pilgrim, Anna; Barker, Mary; Jackson, Alan; Ntani, Georgia; Crozier, Sarah; Inskip, Hazel; Godfrey, Keith; Cooper, Cyrus; Robinson, Sian
Abstract : Background: Little is known about food insecurity in the UK. The aims of this study were to assess the prevalence and factors associated with food insecurity in a UK cohort and to examine whether the diets, reported health and anthropometry of young food insecure children differed from those of other children. Methods: The Southampton Women's Survey is a prospective cohort study in which detailed information about the diets, lifestyle and body composition of 3000 women was collected before and during pregnancy. Between 2002 and 2006, 1618 families were followed up when the child was 3 years old. Food insecurity was determined using the Household Food Security Scale. The child's height and weight were measured; diet was assessed by food frequency questionnaire. Results: 4.6% of the households were food insecure. Food insecurity was more common in families where the mothers were younger, smokers, of lower social class, in receipt of financial benefits and who had a higher deprivation score (all p<0.05). In comparison with other 3-year-old children, those living in food insecure households were likely to have worse parent-reported health and to have a diet of poorer quality, characterised by greater consumption of white bread, processed meat and chips, and by a lower consumption of vegetables (all p<0.05). They did not differ in height or body mass index. Conclusions: Our data suggest that there are significant numbers of food insecure families in the UK. The poorer reported health and diets of young food insecure children have important implications for their development and lifelong health.